INDIGENOUS CHICKEN PRODUCTION IN PUNJAB: A DETAILED SURVEY THROUGH PARTICIPATORY RURAL APPRAISALS - S. Sadef; M.S. Khan; M. S. Rehman (Journal of Animal and Plant Sciences, 2015)
The present study was designed to understand role of indigenous chicken in livelihood of rural masses, traits for which it is preferred and documentation of production constraints at two experimental sites in Punjab (Pakistan) through participatory rural appraisals. Gender sensitivity was accounted for conducting these appraisals. Main purpose of chicken keeping was home consumption and income obtained from extra sale of chicken and eggs was mostly kept by women and household heads which they spent on family needs and investing back on livestock/poultry. Differences among men and women’s perceptions in keeping particular chicken breed and traits were not the same. Fayoumi and Rhode Island Red breeds were preferred for egg production, Desi and Naked Neck for broodiness and disease resistance while Aseel breed was highly ranked for its aggressiveness and economic value. The major constraints at Bahawalpur site were absence of veterinary services and shortage of canal water. Less availability of space and risk of predators were obvious at Faisalabad site. Prevalence of diseases and lack of financial aid was noted at both sites. It was suggested that provision of necessary health coverage and trainings could lead to better chicken production and an income generating activity for landless poors and deprived women of the area.
Keywords: Indigenous chicken; gender; livelihood analysis; PRA; production systems